A Role for PICKLE in the Regulation of Cold and Salt Stress Tolerance in Arabidopsis - Yang, Rong; Hong, Yechun; Ren, Zhizhong; Tang, Kai; Zhang, Heng; Zhu, Jian-Kang; Zhao, Chunzhao (Frontiers in Plant Science, 2019)
Arabidopsis PICKLE (PKL) is a putative CHD3-type chromatin remodeling factor with important roles in regulating plant growth and development as well as RNA-directed DNA methylation (RdDM). The role of PKL protein in plant abiotic stress response is still poorly understood. Here, we report that PKL is important for cold stress response in Arabidopsis. Loss-of-function mutations in the PKL gene lead to a chlorotic phenotype in seedlings under cold stress, which is caused by the alterations in the transcript levels of some chlorophyll metabolism-related genes. The pkl mutant also exhibits increased electrolyte leakage after freezing treatment. These results suggest that PKL is required for proper chilling and freezing tolerance in plants. Gene expression analysis shows that CBF3, encoding a key transcription factor involved in the regulation of cold-responsive genes, exhibits an altered transcript level in the pkl mutant under cold stress. Transcriptome data also show that PKL regulates the expression of a number of cold-responsive genes, including RD29A, COR15A, and COR15B, possibly through its effect on the expression of CBF3 gene. Mutation in PKL gene also results in decreased cotyledon greening rate and reduced primary root elongation under high salinity. Together, our results suggest that PKL regulates plant responses to cold and salt stress.